Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 55003 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Pinales", "Country is United States of America", "HasCoordinate is true" ] } The dataset includes 55003 records from 93 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0004723-160118175350007/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences